A Ni(ii) metal–organic framework with helical channels for the capture of iodine via guest exchange induced amorphization. (25th March 2022) - Huang, Jie-Fen; Hu, Hao-Chen; Deng, Shu-Qi; Cai, Song-Liang; Fan, Jun; Zhang, Wei-Guang; Zheng, Sheng-Run
Abstract : A Ni(ii ) MOF based on a imidazole–tetrazole heterotopic tripodal ligand was constructed. It exhibits abilities for the stable capture of iodine molecules present in cyclohexane, water, and vapor, via amorphization induced by guest exchange. Abstract : Radioactive iodine is a major nuclear waste, and its capture and immobilization are highly desirable. Herein, a new Ni(ii ) metal–organic framework based on a newly designed imidazole–tetrazole heterotopic tripodal ligand, namely, SCNU-Z5, was constructed and applied to the capture of iodine from solution and the vapor phase. SCNU-Z5 has an interesting high-connectivity chiral framework with 1D helical channels. The combination of 1D channels and two other crossed 1D channels resulted in a porous framework with N, N -dimethylacetamide (DMAc) guest molecules. The guest molecules were exchanged by iodine molecules present in cyclohexane, water and vapor, with maximum adsorption capacities of 442, 352, and 1680 mg g −1, respectively. Mechanism studies showed that iodine adsorption was attributed to the charge transfer between iodine molecules and the framework and the interaction of iodine molecules themselves. Interestingly, the adsorption of iodine molecules led to amorphization of the framework, and I2 was buried and fixed stably inside the framework, thus providing a new strategy for stable immobilization of iodine in MOFs.